2007 International Conference on Cyberworlds (CW'07) 2007
DOI: 10.1109/cw.2007.54
|View full text |Cite
|
Sign up to set email alerts
|

MHaptic : a Haptic Manipulation Library for Generic Virtual Environments

Abstract: Abstract-This paper presents a new library called MHaptic for bimanual haptic interaction within generic virtual environments. It has been specifically designed to work with a Haptic Workstation TM . MHaptic provides tools for accelerated development of virtual environment applications with haptic feedback like device calibration, user comfort improvements and access to low level parameters. Due to its integration with the Ageia PhysX library, it facilitates the dynamic animation of virtual objects. A realisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
(14 reference statements)
0
22
0
Order By: Relevance
“…Others are multi-fingered interfaces, such as the MasterFinger-2 [6], SPIDAR-8 [7] and Bimanual HIRO [8], which enable interaction through 4, 8 and 10 fingertips respectively. Within this category of multi-fingered devices, the Haptic Workstation is a special case, not only providing interaction through the fingertips but also through the palm of both hands [9]. Multi-fingered interfaces are especially suited for grasping virtual objects thanks to their numerous interaction points, although it was shown that single-point devices could also allow grasping with a full control of all degrees of freedom (DoF) of an object through a soft-fingers method [10].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Others are multi-fingered interfaces, such as the MasterFinger-2 [6], SPIDAR-8 [7] and Bimanual HIRO [8], which enable interaction through 4, 8 and 10 fingertips respectively. Within this category of multi-fingered devices, the Haptic Workstation is a special case, not only providing interaction through the fingertips but also through the palm of both hands [9]. Multi-fingered interfaces are especially suited for grasping virtual objects thanks to their numerous interaction points, although it was shown that single-point devices could also allow grasping with a full control of all degrees of freedom (DoF) of an object through a soft-fingers method [10].…”
Section: Related Workmentioning
confidence: 99%
“…A straightforward hardware approach consists in increasing the workspace provided by each haptic device to fit that of the VE, either through a bigger frame or a redundant DoF. However the best result obtained for bimanual devices was the reach of human arms, in the cases of the DLR interface [3] and the Haptic Workstation [9]. Another solution for handling large VEs is the use of mobile haptic interfaces, i.e.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The libraries will provide relatively basic haptic features, but they also offer extensibility for customized physical modeling, shape rendering, force effects, collision detection, dynamics and other third-party engines. More haptic modeling libraries are available but not widely applied as the ones listed in Table 1 [57][58][59][60][61].…”
Section: Haptic Modelingmentioning
confidence: 99%
“…We decide to work with the Immersion 3 Haptic Workstation TM instead of other VR haptic devices. In fact, it is a two-armed-based system [11] that allows a well-balanced effort of the patients between their right and left limbs. This avoids excessive torsions and efforts with the spinal column.…”
Section: Introductionmentioning
confidence: 99%